2017
DOI: 10.1590/0102-33062017abb0123
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the effects of fire on branching and leaf development in cerrado trees

Abstract: We discuss evidence of eff ects of an accidental fi re on shoot growth and leaf development in six cerrado tree species with distinct leaf phenologies. Buds of all six species were marked before shoot and leaf emergence in the dry season. After fi re, leaf and shoot growth were monitored weekly and specifi c leaf area (SLA) was determined. Shoot order was determined in the growing season. Evergreens and semideciduous woody species had rapid leaf and shoot growth and decreased leaf life span (LLS) after fi re c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Many researchers have demonstrated that the recovery of branches and leaves was very fast after disturbances. For example, trees can reach the same leaf mass fraction within one year after pruning treatment [35]: evergreens and semideciduous trees showed intense and accelerated shoot and leaf development after fire [36]. A measurement of forest greenness by satellite after the 2008 Chinese ice storm showed a fairly quick overall recovery [11], which indicated a quick leaf recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have demonstrated that the recovery of branches and leaves was very fast after disturbances. For example, trees can reach the same leaf mass fraction within one year after pruning treatment [35]: evergreens and semideciduous trees showed intense and accelerated shoot and leaf development after fire [36]. A measurement of forest greenness by satellite after the 2008 Chinese ice storm showed a fairly quick overall recovery [11], which indicated a quick leaf recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Branches bearing buds with newly formed organs, such as in evergreen trees and semi-deciduous species X. aromatica, T. stenocarpa, S. adstringens and S. polyphyllum, are vigorously produced after heavy rains, with lower activity during the winter drought. Notwithstanding, there is a permanent source of carbon in those evergreen species by the persistent foliage and continuous production of leaves and branches (Damascos et al 2005;Damascos 2008;Souza et al 2017). Thus, evergreen and the majority of semi-deciduous trees study here are less dependent on long-term carbon storage in below-ground organs than deciduous species.…”
Section: Discussionmentioning
confidence: 87%
“…In the Cerrado, vegetation suffers with reduced woody cover and formation of canopy gaps in the months following fires , as detected by the minimum NDVI values used in our analysis (0.369 and 0.458), which corresponded to post-fire months. After a few months of burning, Cerrado vegetation often exhibits regrowth (Souza et al 2017), which in turn, increases the availability of arthropods and seeds (Vasconcelos et al 2009;Diniz et al 2011), frequent items in the diet of R. mastacalis (Sousa et al 2004;.…”
Section: Discussionmentioning
confidence: 99%